Amber Brown is Not a Crayon - Danziger, Paula, 1944- (New York, NY : Putnam's, 1994)
The year she is in the third grade is a sad time for Amber because her best friend Justin is getting ready to move to a distant state.
Keywords: Friendship -- Fiction; Moving, Household -- Fiction; Schools -- Fiction